How to Implement the Family Planning Village Program - Jopang Jopang; Supranoto Supranoto; Sanawia Sanawia (Badan Penerbit STIEPARI Press, 2023)
This study aims to investigate Makassar City's Family Planning Village Program's execution. This study examines the execution of the Family Planning Village Program in Makassar City from a qualitative descriptive perspective. Through documentation, interviews, and observation, data was acquired. The data used in this study are made up of primary data, which are essentially the findings from source interviews, and secondary data, which are supplementary data found through observations and interviews. Interactive data analysis, which involves data reduction, data visualization, and conclusion writing, handles data processing in the interim. This study shows that adequate resources are available and that the Family Planning Village Program in Makassar City is effectively implemented in line with the set aims and objectives.